2021
DOI: 10.1002/lary.29886
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Artificial Intelligence to Office Laryngoscopy: A Scoping Review

Abstract: Objectives/Hypothesis This scoping review aims to provide a broad overview of the applications of artificial intelligence (AI) to office laryngoscopy to identify gaps in knowledge and guide future research. Study Design Scoping Review. Methods Searches for studies on AI and office laryngoscopy were conducted in five databases. Title and abstract and then full‐text screening were performed. Primary research studies published in English of any date were included. Studies were summarized by: AI applications, targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 25 publications
0
23
0
Order By: Relevance
“…17 Emerging work seeks to apply similar analytic techniques to laryngoscopy video. 18 However, efforts in video laryngoscopy have been slower, perhaps as a result of limited data sets as well as the anatomic complexity and dynamic nature of the glottis. Studies (Table 1) used keyframes (informative images) extracted from laryngoscopy videos as data inputs to train ML models.…”
Section: Part 1: Data Modalitymentioning
confidence: 99%
“…17 Emerging work seeks to apply similar analytic techniques to laryngoscopy video. 18 However, efforts in video laryngoscopy have been slower, perhaps as a result of limited data sets as well as the anatomic complexity and dynamic nature of the glottis. Studies (Table 1) used keyframes (informative images) extracted from laryngoscopy videos as data inputs to train ML models.…”
Section: Part 1: Data Modalitymentioning
confidence: 99%
“…However, we examined several recent studies that employed artificial neural networks for the computer-aided diagnosis of laryngeal cancer [ 7 , 20 , 21 , 22 , 23 ] and found that although the datasets were labelled and well-structured, the number of images still ranged from 3000 to 25,000. Such samplings applied to clinical applications are still a considerable workload for science, technology, engineering, and math (STEM) researchers willing to cooperate with physicians [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the public datasets related to informative frame selection are rare, only 3% (3/97) compared to vibration analysis, lesion recognition, etc. [ 24 ]. Our fundamental concern is that existing algorithms are insufficient for extracting specific patterns of high-quality data in enormous data with noise.…”
Section: Introductionmentioning
confidence: 99%
“…Parallelly, the use of AI in videoendoscopy, especially in the gastrointestinal field, has already become relevant in the literature and even on the market ( 18 ). When moving to the specific field of UADT, however, only a few studies have been published in the current literature, with most focusing on laryngeal endoscopy ( 19 ). Among all AI-powered methods, deep learning (DL) techniques based on convolutional neural networks (CNNs) are increasingly used in UADT videoendoscopy analysis for automatic disease detection ( 20 22 ), classification ( 23 , 24 ), and segmentation ( 25 ).…”
Section: Introductionmentioning
confidence: 99%